Pendampingan Transformasi Limbah Minyak Jelantah Menjadi Biodiesel sebagai Upaya Mewujudkan Industri Berkelanjutan - Nurwidiana, Nurwidiana; Fatmawati, Wiwiek; Saputri, Pungky Lela; Hidayat, Taufiq (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
The fried-shallot industry generates large quantities of waste cooking oil, which is commonly stockpiled and, in some cases, distributed to nearby residents for household cooking. This practice poses environmental risks and potential health impacts, asdegraded oil continues to be consumed. These challenges form the basis of this community engagement program, whichaims to support partner enterprises in managing waste cooking oil to prevent negative impacts while transforming it into value-added products. The program aimed to assist the partner in managing used cooking oil into high-value, eco- friendly products in the form of biodiesel. The implementation used the Participatory Rural Appraisal (PRA) approach, emphasizing active participation of the partner in all stages, including socialization on waste management, biodiesel production training, equipment fabrication, and establishment of a biodiesel production unit at the partner’s site. The results showed a significant improvement in the partner’sknowledge and skills in waste management; 100% of the used cooking oil waste was successfully processed into biodiesel, providing additional income opportunities. Moreover, the activity encouraged the industry to operate more sustainably andcontribute to green energy provision. This program demonstrated that technical assistance combined with simple technologycan create an economically and environmentally sustainable production system.